Prevention of Allograft Rejection by Use of Regulatory T Cells With an MHC‐Specific Chimeric Antigen Receptor. Issue 4 (6th February 2017) - Noyan, F.; Zimmermann, K.; Hardtke‐Wolenski, M.; Knoefel, A.; Schulde, E.; Geffers, R.; Hust, M.; Huehn, J.; Galla, M.; Morgan, M.; Jokuszies, A.; Manns, M. P.; et al.
Abstract : CD4 + CD25 high FOXP3 + regulatory T cells (Tregs) are involved in graft‐specific tolerance after solid organ transplantation. However, adoptive transfer of polyspecific Tregs alone is insufficient to prevent graft rejection even in rodent models, indicating that graft‐specific Tregs are required. We developed a highly specific chimeric antigen receptor that recognizes the HLA molecule A*02 (referred to as A2‐CAR). Transduction into natural regulatory T cells (nTregs) changes the specificity of the nTregs without alteration of their regulatory phenotype and epigenetic stability. Activation of nTregs via the A2‐CAR induced proliferation and enhanced the suppressor function of modified nTregs. Compared with nTregs, A2‐CAR Tregs exhibited superior control of strong allospecific immune responses in vitro and in humanized mouse models. A2‐CAR Tregs completely prevented rejection of allogeneic target cells and tissues in immune reconstituted humanized mice in the absence of any immunosuppression. Therefore, these modified cells have great potential for incorporation into clinical trials of Treg‐supported weaning after allogeneic transplantation. Abstract : Reprogramming human regulatory T cells using an HLA‐A*02 chimeric antigen receptor generates highly specific and very potent Tregs able to prevent allogeneic rejection in immune‐reconstituted humanized mice. See the editorial from Ferreira and Tangon page 851 .